Investigação de parasitos e/ou comensais intestinais em manipuladores de alimentos de escolas públicas - da Silva, Éder José; da Silva, Regildo Márcio Gonçalves [UNESP]; Silva, Luciana Pereira [UNESP] (My University, 2009)
The objective of this work was to identify intestinal parasites and/or commensals among food handlers of public schools in the city of Patos of Minas (MG). The fecal samples were analyzed by Lutz's method (1919). The positive results were 21.7% (13 cases) for parasites and/or commensal. The frequence of intestinal parasites and/or commensal of food handlers in the public schools showed low positive, probably as a result of good habits of personal hygiene and prophylactic treatment of parasitic.
Investigation of intestinal parasites and/or commensals in food handlers of public schools
Keywords: Commensal; Food handlers; Intestinal Parasites